Sinkretisme Budaya Islam dan Budaya Lokal Nusantara Dalam Memperkokoh Hubungan Masyarakat - Sri Lestari; Yuyun Yunita (Ri'ayah: Jurnal Sosial dan Keagamaan, 2025)
This research attempts to highlight the syncretism of Islam and local culture that occurs in the reality of society. The focus of this research is what elements of the principles are syncretized with each other, in what ways and at what level the syncretic process occurs. Syncretism is a combination of two opposing elements, initially referring to the unification carried out in political matters, then developing in the field of religion, especially Christianity and Protestantism. The development of today's science that is experiencing ups and downs has also impacted the use of terms that are not only dichotomous in one field but also diverse in nature. The results of this research show that the syncretic elements are in a series of religious rituals, the media used through the externalization of culture. The conclusion of this research is the existence of syncretism between Islamic culture and local culture of the archipelago.